PENGARUH ARUS TABUNG TERHADAP NOISE DAN KONTRAS CITRA PADA PESAWAT CT SCAN - Riyanto, Slamet; Budi, Wahyu Setia; Anam, Choirul (BERKALA FISIKA, 2019)
This study aims to evaluate the effect of tube current on noise and low contrast resolution in CT scan images. Determination of the noise and the low contrast resolution was carried out using the built-in phantom of CT scan. To determine the noise, a phantom section consisting of homogeneous water (water filled phantom) was used, and to determine the low contrast resolution, a phantom section consisting of a polystyrene box was used. The images were taken in an axial mode, using a voltage of 120 kVp, rotation time of 2 seconds, beam collimation of 10x2.5 mm, and slice thickness of 7 mm. The tube current was varied from 80 mA to 200 mA. At each scanning, 3 (three) slices were taken. The results show that an increase of the tube current from 80 mA to 200 mA causes a decrease in THE noise, but does not affect TO the low contrast resolution. At the same low contrast resolution, an increase of the noise decreases object detectability.Keywords: tube current, image noise, low contras resolution, axial scanning, CT scan